2012
DOI: 10.1210/en.2012-1065
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Prevents Incidence of Malignant Arrhythmia after Acute Myocardial Infarction through Vagal Afferent Nerves

Abstract: Ghrelin is a GH-releasing peptide mainly excreted from the stomach. Ghrelin administration has been shown to inhibit cardiac sympathetic nerve activity (CSNA), reduce malignant arrhythmia, and improve prognosis after acute myocardial infarction (MI). We therefore investigated the effects and potential mechanisms of the action of endogenous ghrelin on survival rate and CSNA after MI by using ghrelin-knockout (KO) mice. MI was induced by left coronary artery ligation in 46 KO mice and 41 wild-type mice. On the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 31 publications
0
44
0
2
Order By: Relevance
“…22 In cases of methylatropine bromide (1 mg/kg) administration, it was injected intraperitoneally 5 minutes after the ghrelin injection. 23 …”
mentioning
confidence: 99%
“…22 In cases of methylatropine bromide (1 mg/kg) administration, it was injected intraperitoneally 5 minutes after the ghrelin injection. 23 …”
mentioning
confidence: 99%
“…Costaining with acetylcholine esterase and choline acetyltransferase suggested that GHSR1a is localized on or in close proximity to the vagal nerve terminals in the heart. 60,61 Therefore, substantial evidence indicates that ghrelin has a cardiovascular function.…”
Section: Cardiovascular Activitymentioning
confidence: 99%
“…60,61,70 Ghrelin receptors are synthesized in vagal afferent neurons and are transported to the afferent terminals in the stomach. Ghrelin produced in the stomach stimulates the gastric vagal afferent nerve that leads to the nucleus tractus solitarius, influencing its neuronal activity and increasing feeding behavior.…”
Section: Peripheral Neural Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…GHS-R mRNA is found not only in the hypothalamus and pituitary gland but also in the heart and blood vessels (Gnanapavan et al 2002). Significant evidence for a cardiovascular function of ghrelin and its role in the regulation of autonomic activity has been reported (Soeki et al 2008;Mao et al 2012). Although recent experimental studies have demonstrated that administration of ghrelin could protect against ischemia and reperfusion injury, attenuate post-infarction ventricular dysfunction and remodeling, and improve the prognosis of myocardial infarction and heart failure (Nagaya et al 2001;Chang et al 2004;Schwenke et al 2008;Soeki et al 2008;Mao et al 2012), the role of ghrelin in the clinical setting remains unknown.…”
Section: Introductionmentioning
confidence: 99%